Mid-term and Long-term Functional and Radiographic Results of 13 Surgically Treated Adolescent Capitellum Fractures - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2018)
Background: Capitellum fractures are rare in adolescents, and information in literature is still limited. The purpose of this study was to report the mid-term and long-term functional and radiographic results of 13 surgically treated adolescent capitellum fractures in a level I trauma center. Methods: This retrospective study included patients aged 10 to 16 years, who underwent surgery for a capitellum fracture and were followed up for at least 12 months. Fractures were classified according to the McKee modification of the Bryan and Morrey classification, and elbow arthritis was classified using the Broberg and Morrey system. Functional outcomes were assessed with the Mayo Elbow Performance Index (MEPI) and the Turkish-language version of the shortened version of the Disabilities of Arm, Shoulder, and Hand (QuickDASH) scale. Results: The mean time to surgical intervention was 4.5 days (range, 1 to 18d). The mean flexion-extension range of motion arc was measured as 115 (range, 45 to 150) degrees. The mean restriction for extension and flexion compared with the uninjured side was measured as 10.7 (range, 0 to 45) and 11.5 (range, 0 to 45) degrees, respectively. The mean MEPI was 87.7 points (range, 50 to 100 points) with 9 patients as excellent, 1 good, 1 fair, and 2 poor results. The mean QuickDASH score was 11 (range, 0 to 57). The mean MEPI score was 95.6 and 75 and the mean QuickDASH score was 2.62 and 25.0 for early surgery group (<= 3d) and late surgery group (>3d), respectively (P=0.073, 0.024). Elbow joint contracture developed in 4 patients. Implant removal and open release of joint contracture was applied to 2 patients. Elbow arthritis of grade 3 was observed in 2 patients and grade 2 in 1 patient. Conclusions: Capitellum fractures may be easily missed on conventional radiographs, if not suspected. Delayed diagnosis may lead to a worsening of the functional outcomes. Computerized tomography is helpful in the determination of these fractures. Early diagnosis and a well-performed surgery is essential for successful outcome.
Keywords: adolescent; capitellum fractures; surgery; INTERNAL-FIXATION; OPEN REDUCTION; DISTAL HUMERUS; MANAGEMENT; INJURIES; SCREWS